PENGARUH PERTUMBUHAN EKONOMI TERHADAP KESEMPATAN KERJA DI KOTA PONTIANAK - Jonathan Giovanni; Mochammad Faisal Fadli (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
The study was conducted to examine public perceptions of the magnitude of the effect of economic improvement that occurred in the city of Pontianak on the opening of employment opportunities for the population of the workforce whether they were still in the process of looking for work or who were already working. Data will be obtained through a questionnaire which will be distributed to the speakers who will then be conducted a regression analysis using SPSS. The guest speaker is a workforce community of 384 people who will be divided equally into 6 subdistricts in the city of Pontianak. Where will then be compared with data that has been released by BPS Pontianak about economic levels and unemployment. The results of this study indicate that economic growth in the city of Pontianak was able to trigger a significant growth in the number of new business entities but was only able to influence by 3% for opening employment opportunities. So based on this data it can be a consideration for Pontianak City Government to pay attention to the pattern of absorption of work carried out by business actors so that they can directly contribute to opening employment opportunities and reducing unemployment in Pontianak.